The Parigeuing Leadership: Synergy of Sundanese Cultural Values in Educational Leadership in West Java - Darmawan, Prasetyo Agung; Nurdin, Diding; Sururi, Sururi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Parigeuing leadership, rooted in Sundanese cultural values, underscores a leader’s effective communication rooted in local traditions. This study explores the leadership of the Head of the West Java Provincial Education Office as a representation of educational leadership in Sundanese society, with a focus on communication practices aligned with parigeuing principles. A qualitative case study methodology was employed to gather data through comprehensive, in-depth interviews, direct observations of the leader’s communication style, and document analysis of the manuscript. Seven informants, including division heads, staff members, and a philology expert provided insights into the manifestation of parigeuing leadership. The findings highlight that parigeuing leadership is evident in the leader’s approach to delivering instructions, guidance, and motivation, with dasa pasanta serving as a guiding framework. This study contributes to the theoretical advancement of inclusive educational leadership models grounded in local cultural values, providing practical insights for leaders in Sundanese society and beyond.